Twenty-four months of bacterial colonialization and infection rates in patients with transcutaneous osseointegrated prosthetic systems after lower limb amputation—A prospective analysis - Örgel, Marcus; Aschoff, Horst-Heinrich; Sedlacek, Ludwig; Graulich, Tilman; Krettek, Christian; Roth, Sabine; Ranker, Alexander (Frontiers in Microbiology, 2022)
Background Transcutaneous osseointegrated prosthesis systems (TOPS) are alternative rehabilitation methods to socket prosthetics, after limb amputation. TOPS compromise a two-step surgery: starting with the implantation of the stem which is then followed by the creation of the transcutaneous stoma through which the exoprosthesis can be connected. Immediately after surgery, this opening is permanently exposed to pathogens. This study aimed to investigate the dynamics of bacterial colonization of the stoma to analyze whether obligate bacterial colonization leads to a risk of periprosthetic infections after TOPS treatment. Methods This prospective study analyzed data from 66 patients (aged 26–75 years) after TOPS treatment between 2017 and 2019. Microbiological swabs from the stoma were analyzed on the first postoperative day and 3, 6, 12, and 24 months after stoma creation. Infection rates, laboratory values (CRP, leukocyte count, hemoglobin), and body temperature were recorded at these points in time. Statistical analysis was performed using SPSS 28. Results The results show the formation of a stable environment dominated by Gram-positive bacteria in the stoma of TOPS patients over 24 months. Staphylococcus aureus, Staphylococcus spp., and Streptococcus spp. were the most common species found. With regard to the cohort up to the 3 months follow-up, 7.9% (five patients) developed infections surrounding the TOPS procedure. In relation to the whole cohort with loss to follow-up of 80.3% at the 24 months follow-up the infection rates increased up to 38.3%. Conclusion The soft tissue inside and around the transcutaneous stoma is colonialized by multiple taxa and changes over time. A stable Gram-positive dominated bacterial taxa could be a protective factor for ascending periprosthetic infections and could possibly explain the relatively low infection rate in this study as well as in literature.